Computer-Based Clinical Examination (CCE) in Surgery: Would It Complement or Replace the OSCE in the Post-COVID-19 Era? - Gamal E H A El Shallaly; Mudather M Bafadni; Hozifa M A Abdelmaged; Maysa H A Hamza (Sudan Journal of Medical Sciences)
Objectives: Surgical clinical assessment of medical students is confronted by many challenges particularly the increasing numbers of students with limited resources, and pandemics. The search for new tools of assessment continues. Our objectives were: (1) To develop a computer-based clinical exam (CCE) and identify its characteristics (2) To assess its acceptability of the students. Method: The study was conducted at the Surgical Department, Alzaiem Alazhari University (AAU) between February and August, 2017. We used the modular objectoriented dynamic learning environment (MOODLE) program as a platform to upload and deliver the exam. The exam consisted of 45 questions (stations). Each consisted of a clinical scenario accompanied by a photograph (of a patient or investigation) or short video followed by multiple choice questions (MCQs). A questionnaire was designed to get the students’ feedback. We analyzed the questionnaire and scores obtained by the students and compared them to their performance in other tools of the surgical exam, using SPSS statistical program. Results: The study included 188 final year medical students. There was a highly significant correlation of the CCE scores of each student with their final result (r= 0.67), and with other tools of the surgery exam particularly the objective structured clinical examination (OSCE). Students’ acceptability was high. Conclusion: The CCE is valid and practicable. It saves time and is popular with the students and tutors. It complements the OSCE in the assessment of clinical competency and allows wide coverage of the curriculum. It is expected to gain importance and popularity in the post-COVID-19 era.